2021
DOI: 10.1093/g3journal/jkab053
|View full text |Cite
|
Sign up to set email alerts
|

Genome announcement ofSteinernema khuongiand its associated symbiont from Florida

Abstract: Citrus root weevil (Diaprepes abbreviates) causes significant yield loss in citrus, especially in Florida. A promising source of control for this pest are biological control agents, namely, native entomopathogenic nematodes (EPN) within the genus Steinernema. Two species of endemic EPN in Florida are S. diaparepesi, abundant within the central ridge, and S. khuongi, dominating the flatwood regions of the state. These citrus-growing regions differ significantly in their soil habitats, which impacts the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…2019; Baniya et al . 2019; Baniya and DiGennaro 2021). Because the skpo-2 locus is X-linked in both S. hermaphroditum and S. carpocapsae , it is hemizygous in males; it is likely also X-linked in all other Steinernema nematodes, whose X chromosomes have not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2019; Baniya et al . 2019; Baniya and DiGennaro 2021). Because the skpo-2 locus is X-linked in both S. hermaphroditum and S. carpocapsae , it is hemizygous in males; it is likely also X-linked in all other Steinernema nematodes, whose X chromosomes have not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
“…The skpo-2 locus is exceptionally well suited to serve as such as a marker: we could readily recover Shm-skpo-2 mutants on the basis of their easily recognized phenotype, and Shm-skpo-2 dumpy mutants are healthy and mate well as males. In each of the seven Steinernema species for which sequence is available, there is one skpo-2 gene (Dillman et al 2015;Serra et al 2019;Baniya et al 2019;Baniya and DiGennaro 2021). Because the skpo-2 locus is X-linked in both S. hermaphroditum and S. carpocapsae, it is hemizygous in males; it is likely also X-linked in all other Steinernema nematodes, whose X chromosomes have not yet been identified.…”
Section: Prospects For Crispr-cas9 Gene Targeting In Steinernemamentioning
confidence: 99%
See 1 more Smart Citation
“…Genome completeness using Core Eukaryotic Genes Mapping Approach (CEGMA) (Parra et al, 2007) against 248 ultra-conserved core eukaryotic genes showed 97.17% completeness. A total of 10,494 protein-coding genes were predicted in the H. indica Hms1-i20 by SNAP (Korf, 2004), Augustus (Stanke and Morgenstern, 2005), GeneMark (Besemer and Borodovsky, 2005), and Maker (Cantarel et al, 2008). Functional annotation by NCBI Blastx+/ RefSeq/SwissProt/UniProt databases resulted in the annotation of 9,596 genes.…”
Section: Journal Of Nematologymentioning
confidence: 99%
“…Genomic information about EPNs is scant in the public domain. Presently, whole-genome information is available for only one heterorhabditid and seven steinernematid nematodes ( Lu et al, 2016 ; Baniya and DiGennaro, 2021 ). Here, we present the first draft genome sequence assembly for Heterorhabditis indica , which is widely present in the warmer and tropical climatic regions and is one of the most commercialized EPNs ( Lacey and Georgis, 2012 ).…”
mentioning
confidence: 99%